2022
DOI: 10.1158/1055-9965.epi-21-1003
|View full text |Cite
|
Sign up to set email alerts
|

Beyond GWAS of Colorectal Cancer: Evidence of Interaction with Alcohol Consumption and Putative Causal Variant for the 10q24.2 Region

Abstract: Background: Currently known associations between common genetic variants and colorectal cancer explain less than half of its heritability of 25%. As alcohol consumption has a J-shape association with colorectal cancer risk, nondrinking and heavy drinking are both risk factors for colorectal cancer. Methods: Individual-level data was pooled from the Colon Cancer Family Registry, Colorectal Transdisciplinary Study, and Genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…DNA mismatch repair gene mutation carriers are more susceptible to alcohol-induced CRC. 94 A genome-wide study indicated a possible interaction between alcohol intake and genetic variants in the 10q24.2/COX15 region, 95 and the A allele of single nucleotide polymorphisms rs2300985 has an increased risk for CRC in light-to-moderate drinkers. For heavy alcohol consumption, however, higher risk and worse prognosis of CRC might be associated with hypomethylation of insulin-like growth factor 2.…”
Section: Alcohol-associated Colon Cancermentioning
confidence: 99%
“…DNA mismatch repair gene mutation carriers are more susceptible to alcohol-induced CRC. 94 A genome-wide study indicated a possible interaction between alcohol intake and genetic variants in the 10q24.2/COX15 region, 95 and the A allele of single nucleotide polymorphisms rs2300985 has an increased risk for CRC in light-to-moderate drinkers. For heavy alcohol consumption, however, higher risk and worse prognosis of CRC might be associated with hypomethylation of insulin-like growth factor 2.…”
Section: Alcohol-associated Colon Cancermentioning
confidence: 99%
“…All models included the following set of adjustment covariates—age, study, and ancestry as defined by the first three principal components. Analyses using similar adjustment covariates were used in a recent investigation of G× $G\times $ Alcohol interaction in these data Jordahl et al (2022).…”
Section: Application To Crcmentioning
confidence: 99%
“…All models included the following set of adjustment covariates - age, study/genotyping batch, and ancestry as defined by the first three principal components. Analyses using similar adjustment covariates were used in a recent investigation of G× Alcohol interaction in these data Jordahl et al (2022).…”
Section: Application To Colorectal Cancermentioning
confidence: 99%
“…Bonferroni: Standard Bonferroni correction within bin; simpleM : The simpleM procedure proposed by Gao et al (2008) as defined by the first three principal components. Analyses using similar adjustment covariates were used in a recent investigation of G×Alcohol interaction in these data Jordahl et al (2022). Similar to the simulation study, bin significance threshold cutoffs for SB-weighted testing were based on cutoffs τ = (0, 5/M, 15/M, 35/M, .…”
Section: Application To Colorectal Cancermentioning
confidence: 99%